Incidence and predictors of recurrent and other new diabetic foot ulcers: a retrospective cohort study. Issue 11 (3rd May 2019) - Engberg, S.; Kirketerp‐Møller, K.; Ullits Andersen, H.; Rasmussen, A.
Abstract: Aims: To estimate progression rates, evaluate risk factors for progression, and study rate ratios for progression among people with a healed diabetic foot ulcer according to whether the healed ulcer was neuropathic, neuro‐ischaemic or critically ischaemic. Methods: We conducted a retrospective cohort study in all individuals with a healed diabetic foot ulcer treated at the Steno Diabetes Centre Copenhagen foot clinic in the period 2010 to 2016. The outcome of interest was recurrent/other new diabetic foot ulcers. Results: A total of 780 people had a healed diabetic foot ulcer in the study period (2010–2016). The participants were followed for 1249 person‐years [median (Q1–Q3) 1.04 (0.38–2.46) person‐years] in total. One‐third (33.1%) developed a recurrent/other new diabetic foot ulcer per year. Male gender, people with Type 2 diabetes and smokers had a statistically significantly higher risk of progression to a recurrent/other new diabetic foot ulcer compared to participants without these risk factors. Participants with neuro‐ischaemic or critically ischaemic diabetic foot ulcers had statistically significantly higher progression rates than participants with neuropathic diabetic foot ulcers. Conclusions: Focus should be on preventing future recurrent/other new diabetic foot ulcers especially in people with ischaemia. What's new?: One‐third of the participants with a healed diabetic foot ulcer in the present study progressed to a recurrent/other new diabetic foot ulcer per year. Male gender, Type 2 diabetes and smoking were statistically significant risk factors for a recurrent/other new diabetic foot ulcer. Participants with a neuro‐ischaemic or critically ischaemic diabetic foot ulcer progressed to a recurrent/other new diabetic foot ulcer at a statistically significantly higher rate than participants with neuropathic diabetic foot ulcers, after adjustment for relevant confounders. Focus should be on preventing future recurrent/other new diabetic foot ulcers, especially in people with ischaemia.